Novel N-(2-Methoxydibenzofuran-3-yl)-2-aryloxyacetamide Derivatives: Synthesis and Biological Investigation - Yurttaş, Leyla; Çavuşoğlu, Betül K.; Temel, Halide Edip; Çiftçi, Gülşen Akalın (Letters in Drug Design & Discovery, 2021)
Background: Dibenzofuran ring is a typical heterocyle that is found in many natural sources and its derivatives exhibit a wide scale of biological applications similar to its analog ring systems; furan and benzofuran. Materials and Methods: Novel N-(2-methoxydibenzofuran-3-yl)-2-aryloxyacetamide derivatives (2a-l) were synthesized and evaluated for their cytotoxic activity against A549 lung cancer and NIH/3T3 mouse embryofibroblast cell lines. The inhibition percentages of cathepsin D, L, acetylcholinesterase (AChE) and butrylcholinesterase (BuChE) enzymes provoked by the compounds were also determined. Results and Discussion: Most of the compounds exhibited significant cytotoxicity whose IC50 values were identified lower than the tested lowest concentration (<3.90 μg/mL). Compound 2i against cathepsin D and compound 2k against cathepsin L displayed the highest inhibitory activity. Regrettably, the compounds demonstrated very weak AChE and BuChE inhibition. Conclusion: Compounds 2b, 2c, 2e, 2i and 2k exhibited the highest antiproliferative activity against A549 cell lines with selective profile. However, they did not display satisfying results on tested enzymes.
Keywords: cytotoxicity